PENGARUH EKSTRAKSI DAN PENGERINGAN TERHADAP DERAJAT PEMBAHASAN PERMUKAAN DAN KETEGUHAN REKATAN KAYU (The effect of extraction and oven-drying on wood surface wettability and bond strength) - Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Wood blocks measuring 10 min (radial) x 25 mm (tongitudinal) of regrowth karri (eucalyptus diversicolor F. musfi.) and jarrah (E.marginata ex sm.) were used in this study. The extraction treatment was preceded by a preliminary experiment to determine the effect of extraction on percentage weight loss of wood blocks and extractive yield. Five extraction times were used, 8,16,32,64 and 128 hours, further experiments were undertaken to investigate the effects of oven-drying hot-water extraction an a combination of the two treatments on wattability and shear strength of karri and jarrah laminates, panels were made by gluing pairs of laminates with resorcinol formaldehyde at a spread rate of 1.2 mg/mm2. The preliminary experiment showed that water soluble extractives removed from wood blocks increased with increasing time of extraction. The amount of extractives removed was approximately three times greater is karri than in jarrah. Extending the extraction period beyond 32 hours resulted in collapse, bowing and checking of the wood blocks during drying. Results from the initial experiments revealed that either oven drying, extraction or the combination of the two treatments have all significantly (p<0.01) reduced wettability and shear strength of the wood laminates. There was no significant relationship between wettability and shear strength for both regrowth eucalyptus.